1998
DOI: 10.1002/(sici)1097-4555(199804)29:4<297::aid-jrs240>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic studies of silk fibroin fromBombyx mori

Abstract: This study was focused on the conformational characterization of Bombyx mori silk Ðbroin in Ðlm, Ðber and powder form by means of Fourier transform Raman spectroscopy. Native and regenerated silk Ðbroin Ðlms prepared by casting dilute silk Ðbroin solutions (AE1% , w/v) display characteristic conformationally sensitive bands at 1660 cm-1 (amide I), in the range 1276-1244 cm-1 (a complex amide III region with multiple detectable maxima) and at 1107 and 938 cm-1. This spectral pattern can be related to a prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 12 publications
13
132
1
Order By: Relevance
“…In particular, the I 850 /I 830 ratio allows to study the hydrogen-bonding state of protein's tyrosine phenoxyl group-a more hydrophobic tyrosine environment (i.e., reduction of structural water in the protein) corresponds to higher I 850 /I 830 ratio (25,32). The analysis of the Amide III scattering showed a Raman shift to lower wavenumbers during the water evaporation process, which is an indication of increased β-sheet formation during the gel-solid process (26,27). The study of the I 850 /I 830 ratio during the gel-solid transition showed that the ratio increased during water evaporation, which can be considered as an indication of increased structural hydrophobicity that can be correlated with a more "crystalline" silk configuration.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, the I 850 /I 830 ratio allows to study the hydrogen-bonding state of protein's tyrosine phenoxyl group-a more hydrophobic tyrosine environment (i.e., reduction of structural water in the protein) corresponds to higher I 850 /I 830 ratio (25,32). The analysis of the Amide III scattering showed a Raman shift to lower wavenumbers during the water evaporation process, which is an indication of increased β-sheet formation during the gel-solid process (26,27). The study of the I 850 /I 830 ratio during the gel-solid transition showed that the ratio increased during water evaporation, which can be considered as an indication of increased structural hydrophobicity that can be correlated with a more "crystalline" silk configuration.…”
Section: Resultssupporting
confidence: 87%
“…1B). In particular, the study of the Raman shifts in the Amide I (1,700-1,600 cm (26)(27)(28). The interplay between silk fibroin and water during the material fabrication process was investigated through differential scanning calorimetry (DSC) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The water-insolubility of these silk films after water annealing (but in the absence of methanol treatment) appears to be due to the formation of a stable silk I structure. [25,26] In order to induce the silk II structure, physical shear (between glass slides), physical stretching, or methanol treatments were used. However, once the silk films had significant silk I structural content, there was no transition to silk II, even with methanol (50 %) treatment (Fig.…”
Section: Resultssupporting
confidence: 81%
“…The amide I band appeared at 1665 cm -1 , and the amide III range showed a complex structure at 1277 and 1243 cm -1 . [28] This was a characteristic spectral pattern of SF with a prevailing silk I conformation, in good agreement with the IR results. After PPy deposition, the typical bands of PPy located at 1570 and 1324 cm -1 , assigned to C=C backbone stretching and ring-stretching were observed.…”
Section: Preparation and Characterization Of Sf-ppy Filmsupporting
confidence: 87%